Обследование кабелей с резиновой изоляцией в процессе старения - Федяй, А. С.; Швидкой, А. В. (НТУ "ХПИ", 2009)
Состояние кабелей оценивается путем измерения электрических характеристик в процессе старения. При обследовании контрольных кабелей сложных конструкций применяя схемы совокупных измерений можно зондировать различные изоляционные промежутки кабеля.

Cables state is estimated by measuring of electric characteristics in the process of their senescence. At the inspection of control cables of complex designs it is possible to explore their different isolating intervals applying combined measuring schemes.
Inspection of cables with rubber isolation in the process of senescence
Keywords: каучук; электрические характеристики; кабели сложных конструкций; изоляционные промежутки; диэлектрические потери кабеля; cables; rubber isolation; senescence; electric characteristics